Decreasing incidence of severe malaria and community-acquired bacteraemia among hospitalized children in Muheza, north-eastern Tanzania, 2006-2010 - Mtove, G; Amos, B; Nadjm, B; Hendriksen, I; Dondorp, A; Mwambuli, A; Kim, DR; Ochiai, R; Clemens, J; Von Seidlein, L; Reyburn, H; Deen, J (BioMed Central, 2011)
Background: The annual incidence and temporal trend of severe malaria and community-acquired bacteraemia during a four-year period in Muheza, Tanzania was assessed. Methods. Data on severely ill febrile children aged 2 months to 14 years from three prospective studies conducted at Muheza District Hospital from 2006 to 2010 was pooled and analysed. On admission, each enrolled child had a thin and thick blood film and at least one rapid diagnostic test for falciparum malaria, as well as a blood culture. The annual incidence of bacteraemia and severe malaria among children coming from Muheza was calculated and their temporal trend was assessed. Results: Overall, 1, 898 severe falciparum malaria and 684 bacteraemia cases were included. Of these, 1, 356 (71%) and 482 (71%), respectively, were from the referral population of Muheza. The incidence of falciparum malaria and all-cause bacteraemia in Muheza decreased five-fold and three-fold, respectively, from the first to the fourth year of surveillance (p < 0.0001). During this period, the median ages of children from Muheza admitted with severe malaria increased from 1.7 to 2.5 years (p < 0.0001). The reduction in all-cause bacteraemia was mainly driven by the 11-fold decline in the incidence of non-typhoidal salmonellosis. The annual incidences of Haemophilus influenzae and pneumococcal invasive bacterial infections decreased as well but were much fewer in number. Conclusions: These results add to the growing evidence of the decline in malaria associated with a decrease in non-typhoidal salmonellosis and possibly other bacteraemias. Malarial prevention and control strategies may provide a greater benefit than the mere reduction of malaria alone. © 2011Mtove et al; licensee BioMed Central Ltd.